“It takes A Village”: An Examination of Intra-local Collaborative Economic Development Practices in Ontario, Canada, during the COVID-19 Pandemic - Sutton, Jesse; Lambert, Kavanagh; Arku, Godwin (Canadian Journal of Regional Science / Revue canadienne des sciences régionales)

(untitled) (Canadian Regional Science Association / Association canadienne des sciences régionales, 2022)
Economic development practitioners have traditionally acted in isolation from their local counterparts, such as community organizations, businesses, and other municipal agencies. This type of economic development practice hinders practitioners’ ability to access available resources in their local economy and effectively undertake economic development. Local practitioners in Ontario, Canada, are no exception, as they typically engage in siloed economic development practices, characterized by a general lack of intra-local collaboration. The aim of this paper is to determine if the COVID-19 pandemic has facilitated local practitioners’ economic development practices in Ontario towards intra-local collaboration. To do so, thirty-seven in-depth interviews were conducted with senior local development practitioners in Ontario during the pandemic. The findings indicate that intra-local collaboration had been occurring in localities to a limited extent prior to the pandemic, but has since been intensified, despite several barriers. The gravitation towards intra-local collaboration was motivated by the tremendous challenges brought about by the pandemic, but underpinned by the realization that effective economic development cannot be undertaken in isolation, requiring collective engagement by local actors. During the pandemic, the practitioners intensified their intra-local collaborative practices to increase their access to available local resources, enhance their learning of best practices and acquisition of knowledge, and address common issues faced by various local actors.